The journey to crime and victimization - Luo, Fei (International journal of police science & management, 2021)
The offender’s journey to crime has attracted much attention in mobility triangle research, whereas the journey to victimization and the spatial distance between the offender’s and the victim’s residences have been relatively less examined. This research fills this gap in the literature by examining spatial comparisons of variations in journey to crime, journey to victimization, and the distance between victim’s and suspect’s residences for five types of offenses. Crime data from the Houston Police Department from 2010 to 2013 were used to analyze the mobility triangle in five types of crime. The results show that the dynamics of travel pattern vary by demographic characteristics of the suspects and victims. It is also contingent on the types of crime. The proximity of offender’s and victim’s residences is closely related to the chance of crimes. The findings provide important implications for theory, policy and policing practice.